Relações do Processo de Cooperação Universidade-Empresa: um estudo de caso no interior do Paraná - Silva, Luciane Fontana Matoso (2018)
This study was based on the relations established in the process of University-Company cooperation (U-C), taking as a basis the Theory of Triple Helix, in which the government, university and company are spheres that overlap, each propeller can influence the other, creating new relationships. Such interactions aim at the generation of innovation, in which the university is responsible for the transfer of knowledge, the company seeks the economic development through innovation and the government contributes with incentives and support to public policies. These relationships may influence the effective collaboration between the parts, therefore, the need to study them in accordance with their size, their conditioning and their characteristics. In this perspective, it was considered that the cyclical phases may constitute the process of cooperation U-C, being them, the negotiation, the commitment and the execution. Thus, the general objective of this study was to analyze the relations of cooperation established between the actors of a public university in the interior of Paraná and the companies incubated during the process of technology transfer. To this end, the methodology adopted was a qualitative approach, of a descriptive and analytical nature. As a strategy, the case study was used in a transverse way, having as primary data the collection of semi-structured interviews with the actors of U-C cooperation: managers of incubated and graduated companies, researchers and directors of the innovation agency. Secondary data were collected from publications and previous research on the innovation agency studied, as well as the information of the website of the agency. In addition, the non-participant observation was made with a record in the field diary and triangulation of data. The content analysis involved the pre-analysis phases; exploration of the material and treatment of results: the inference and the interpretation of the data collected. The main results demonstrated that the university plays its role by providing support to companies and involving researchers in the innovation environment. However, it has been realized that the university faces many challenges in terms of lack of academic awareness and social participation in activities related to innovation. It was verified that the government is little perceived in the Triple Helix, it is believed that this result has been influenced by the government's performance as an adjunct to the U-C cooperation. It is inferred that there are still lacks of public policies and effective participation of the government, mainly in encouraging an educational training on innovation. It was noted that the directors' view on the transfer of technology differs from the literature that composes this study, because the leaders believe that the transference occurs when the graduated companies or other companies outside the incubation process seek the agency to establish partnerships in the development of their innovations. It was concluded that the U-C relationship of the processes studied can be considered effective and there is mutual satisfaction among those involved.